The meaning of participation in transitional justice: a conceptual proposal for empirical analysis - Evrard, Elke (International journal of transitional justice, 2021)
Much has been written about the potential of participatory approaches to entrench and expand transitional justice processes. Yet, evidence-based research on how to understand, organize and evaluate victim participation has lagged behind. Empirical research, moreover, often lacks an explicit conceptualization of participation or adopts existing models that start from an institutional perspective and that normatively hierarchize forms and functions of participation. This article, instead, proposes an actor-oriented analytical framework that outlines participants’ trajectories throughout the transitional justice ecosystem. This framework invites a more rigorous investigation of (a) participants’ identities and interests, (b) the spaces they navigate, (c) the relation between various interests, spaces and temporalities and (d) the open-ended nature of outcomes. We apply this framework to Guatemalan indigenous women’s quest for redress for conflict-related sexual violence. The framework facilitates a different way of understanding impact, rooted in local actors’ multidirectional, context-specific and non-linear engagement with transitional justice.